IDO1 promotes Echinococcus multilocularis infection by regulating the formation of neutrophil extracellular traps - Haining Zhang; Ru Meng; Fan Zhang; Ao Chen; Hongrun Ge; Wangkai Chen; Zhi Li; Yong Fu (Veterinary Research)
Abstract The widespread prevalence of alveolar echinococcosis (AE) caused by Echinococcus multilocularis infection poses a significant threat to human health. E. multilocularis is found primarily in the Northern Hemisphere. Given the limitations of current treatment methods, primarily surgical resection, there is a pressing need for more effective therapeutic options. We established a mouse model of E. multilocularis infection by injecting E. multilocularis protoscoleces into C57BL/6 mice. The formation of neutrophil extracellular traps (NETs) following E. multilocularis infection was identified and validated using various techniques, including transcriptome sequencing, scanning electron microscopy (SEM) and flow cytometry. We found that the knockout of the Indoleamine 2, 3 dioxygenase 1 (IDO1) gene or the administration of IDO1 inhibitors resulted in a decrease in the levels of NET-related molecules, including CitH3, MPO, PAD4, PR3, NE, and MPO–DNA complexes, as well as cfDNA. In addition, after the addition of the IDO1 inhibitor, the levels of p65, phospho-p65, p50/105, and REL increased. These results showed that IDO1 promotes the formation of NETs and inhibits NF-κB activation. Moreover, IDO1 inhibits AE progression by regulating NET formation. In conclusion, this study revealed that IDO1 inhibits AE progression by regulating NET formation, and this regulation may be associated with IDO1-induced neutrophil production and NF-κB signalling activation. These results are valuable for understanding the pathogenesis of E. multilocularis and may offer new insights for the prevention and treatment of AE.